Effects of Three Drying Treatments on the Polyphenol Content, Antioxidant and Antimicrobial Properties of Syzygium aromaticum Extract - Tan, Suat Hian; Karim, Md. Rezaul (Chiangmai University, 2018)
Clove (Syzygium aromaticum) is widely accepted as an ancient and most valuable spice of the Orient. Drying process often affects the antioxidant and antimicrobial properties of the spices and solvent has immense impact on the extractability of phytochemicals. This work explored the water extractability of the phenolics from 3 different tissues (unripe fruit, leaf and stem) of the Malaysian grown clove after 3 drying treatments. The study also evaluated the effects of 3 drying processes (microwave-, oven- and air-drying) on the antioxidant and antibacterial properties of the extracts. The fruit extract exhibited highest total phenolic contents (TPC), caffeoylquinic acid (CQA), total vitamin C contents and antibacterial activity, followed by leaf and stem. On the other hand, total flavonoid content (TFC) was highest in leaf extract, followed by fruit and stem. It was found that the polyphenol contents correlated well with their antioxidant activities as determined by using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. Microwave-drying was found to be the most effective to maintain the antioxidant and antibacterial properties of unripe fruit, leaf and stem of the plant. Methanolic extract of all 3 tissue extracts were found to be active against both Gram-positive and Gram-negative bacteria. The extract was found to be more active against Pseudomonas aeroginosa, Escherichia coli and Staphylococcus aureus compared to Bacillus subtilis. It can be concluded from the results that the microwave drying can be the method of choice to maintain the quality of the spice in terms of its antioxidant and antimicrobial properties. The results also demonstrated that water can be used effectively to extract the valuable antioxidants that are beneficial to human health.